Contractual Incentive Provision and Commitment in Rent-Seeking Contests - Oliver Gürtler (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
In this paper, we consider a symmetric rent-seeking contest, where employees lobby for a governmental contract on behalf of firms. The only verifiable information is which firm is assigned the contract. We derive the optimal wage contracts of the employees and analyze, whether commitment by determining the wage contract prior to the competitor is profitable. This is indeed the case, i.e. firms prefer to move first in the wage-setting subgame. This complements previous work on rent-seeking contests emphasizing that commitment via rent-seeking expenditures is unprofitable in symmetric contests.
urn:nbn:de:bvb:19-epub-13451-4
Keywords: D72; M52; 330; Contest; First-Mover Advantage; Commitment; Wage Contract